A Chromosome-Level Genome of the Agile Gracile Mouse Opossum (Gracilinanus agilis). (10th July 2021) - Tian, Ran; Han, Kai; Geng, Yuepan; Yang, Chen; Guo, Han; Shi, Chengcheng; Xu, Shixia; Yang, Guang; Zhou, Xuming; Gladyshev, Vadim N; Liu, Xin; Chopin, Lisa K; et al.
Abstract: There are more than 100 species of American didelphid marsupials (opossums and mouse opossums). Limited genomic resources for didelphids exists, with only two publicly available genome assemblies compared with dozens in the case of their Australasian counterparts. This discrepancy impedes evolutionary and ecological research. To address this gap, we assembled a high-quality chromosome-level genome of the agile gracile mouse opossum ( Gracilinanus agilis ) using a combination of stLFR sequencing, polishing with mate-pair data, and anchoring onto pseudochromosomes using Hi-C. This species employs a rare life-history strategy, semelparity, and all G. agilis males and most females die at the end of their first breeding season after succumbing to stress and exhaustion. The 3.7-Gb chromosome-level assembly, with 92.6% anchored onto pseudochromosomes, has a scaffold N50 of 683.5 Mb and a contig N50 of 56.9 kb. The genome assembly shows high completeness, with a mammalian BUSCO score of 88.1%. Around 49.7% of the genome contains repetitive elements. Gene annotation yielded 24, 425 genes, of which 83.9% were functionally annotated. The G. agilis genome is an important resource for future studies of marsupial biology, evolution, and conservation.